The Influence of Credit Risk, Liquidity Risk, and Capital Adequacy on Financial Performance in the Banking Sector Listed on the Indonesia Stock Exchange 2016-2020 Period: Before and During Covid-19 - Lora Fitria Sari; Fany Alfarisi; Fajri Adrianto (Enrichment : Journal of Management, 2022)
Financial performance in a bank can be measured by return on assets. Return on assets can be used to measure the effectiveness of a company in achieving profits by utilizing its assets. This study aims to determine the effect of NPL, LDR, CAR, Bank Size, and BOPO on financial performance. This study also aims to determine the effect of the Covid-19 pandemic before and during the COVID-19 pandemic. This research was conducted on banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2016 – 2020. The sample was determined using the purposive sampling method and the number of samples selected was 37 banks. The data collection used is secondary data. The data analysis technique used is Penel data regression analysis. The results of the analysis of this study indicate that the first hypothesis is found that credit risk has a negative and significant effect on financial performance. The second hypothesis finds that liquidity risk has a negative and insignificant effect on financial performance. And the third hypothesis is that it is found that capital has a negative and significant effect on financial performance. The results of the fourth test of the four control variables have a positive and significant effect on financial performance, the fifth hypothesis has a negative and significant effect on financial performance. Subsequent research results from 37 banks showed that CAR had differences in financial performance before and during the COVID-19 period, while NPL, LDR, Bank Size.